Synthesis and characterisation of new bismuth phosphate sillenite materials - Lee, Siew Ling; Lee, Chnoong Kheng; Derek C., Sinclair (Penerbit Universiti Sains Malaysia, 2004)
Sillenite compounds, Bi12MO20, where M = Ge, Si, Ti, P, Pb, B (Lobato et al., 2000; Valent and Suvorov, 2001; Valent and Suvorov, 2002; Wignacourt et al., 1991; Marinova et al., 2002) have been studied for their electro-optical, photoconductivity and dielectric properties.